Chinese herbal medicine as maintenance therapy for improving the quality of life for advanced non-small cell lung cancer patients. (February 2016) - Han, Yan; Wang, Huan; Xu, Weiru; Cao, Bangwei; Han, Lei; Jia, Liqun; Xu, Yongmei; Zhang, Qing; Wang, Xiaoming; Zhang, Ganlin; Yu, Mingwei; Yang, Guowang
Highlights: CHM may be considered as maintenance therapy for advanced NSCLC patients. CHM as maintenance therapy may have a potential to prolong PFS time for advanced NSCLC. CHM as maintenance therapy may be beneficial in improving the QOL for advanced NSCLC. CHM is well tolerated. Abstract: Objective: The purpose of the study was to assess the efficacy and safety of using Chinese herbal medicine (CHM) as maintenance therapy considering the survival of advanced non-small-cell lung cancer (NSCLC) patients after first-line conventional platinum-based chemotherapy. Design: An open-label, randomized, controlled trial. Setting: Four hospitals in China. Interventions and main outcome measures: A total of 106 patients were eligible and randomly divided into two groups from four hospitals in China. Both groups received the best supporting care (BSC). Additionally, patients in the trial group were given CHM every day until the disease became aggravated or the patients resigned. The study took both progression-free survival (PFS) and quality of life (QOL) as the primary outcomes to comprehensively evaluate the effect of the treatment. QOL was measured by the Functional Assessment of Cancer Therapy-Lung (FACT-L) 4.0 questionnaire. Side effects and safety were evaluated at the same time. Results: Of the 106 patients, 99 completed the study. After treatment and follow-up for PFS, there were no significant differences in the median PFS time and the 6-month PFS probability between the two groups. However, the 3-month PFS probability in the trial group was significantly higher than that in the control group (FAS, PPS: P  < 0.01). For QOL, there were significant differences between the two groups in the following: physical well-being, emotional well-being, functional well-being, lung cancer symptom domain and total score of the FACT-L4.0 (FAS, PPS: P  < 0.05). There was no significant difference in the social well-being domain. No serious adverse side effects to the treatment were observed. Conclusions: CHM is well tolerated and may improve the QOL of advanced NSCLC patients. CHM is worth studying in future investigations.